The Effect of different concentration of growth regulater on micropropagtion of Lisianthus (Eustoma grandiflora) - Baghdad Science Journal (مجلة بغداد للعلوم)
Plant tissue culture techniques were exploited for the micropropigation of Lisianthus (Eustoma grandiflora). Different concentrations of Benzyl adenine (BA), 6- Furfural amino purine (Kinetin), Indol butyric acid (IBA), were investigated in their effects at different micropropagation stages. Three explants (apical shoots, internodes, leaf discs) were used in this study. The effect of the interaction between BA and IBA on shoot multiplication was investigated in increasing the number of shoots on explants. Rooting was also studied after inclusion of IBA and NAA to Murashige and Skoog, 1962 culture medium (MS). During acclimatization stage, different ratios of river sand and peat moss as agricultural media were tested and plantlets survival was recorded. Maximum mean shoot number was recorded when leaf discs were cultured on MS medium supplemented with 0.3 mg/l of BA giving 6.8 shoots. Highest mean shoot length was obtained when BA at 0.1 mg/l was added to the culture medium giving 1.16 cm. Internodes achieved maximum mean shoot length reached 1.6 cm in the medium supplemented with 0.1 mg/l of BA, while the same concentration of KIN extended the mean shoot length up to 1.6 cm. Shoots that transferred to MS medium containing 1.0 mg/l of IBA achieved the highest root number (5.5) with mean length of 2.5 cm and achieved 70% rooting percentage. Plantlets were acclimatized achieving 90% survival when transferred to agricultural medium consisted of rivers and peat moss at 2:1 v/v ratio.